The consequences of choosing and specifying brand colors directly from a screen – and the need for brand color management - Pedersen, Michael Abilgaard (Journal of Print and Media Technology Research, 2022)
This paper examines some of the implications of choosing brand colors directly from a software program, based on what the designer sees on the screen. The reason is that more and more graphic arts designers tend to choose colors directly from the screen and to a lesser extent from a physical color catalog such as the Pantone fans. Therefore, designers do not really know what color they have chosen until it is available in the final printed form and this can bring unpleasant surprises. The starting point for this study was the digital solutions from Adobe CC and the web service Pantone Connect. The focal point was sRGB, as Pantone recommends, which also is the standard for internet and mobile devices. Initially, the problem with using a small color space as sRGB to select and define brand colors was investigated. Examples of Pantone colors outside sRGB gamut but still available for the designer to choose without any warnings, have been sought. For example, if the designer chooses Pantone Green C as a brand color, the result would be a color difference of 10.5 ΔE00. The CIELAB values for a color defined in sRGB were compared to the CIELAB reference values for the same color as it will appear as a printed spot color. This gives a color difference ΔE00 between how the color appears on the screen versus the physical color as it appears on a print, printed as 1-color solid spot color. Pantone Connect’s feature for converting colors from sRGB to Pantone Solid spot color is also investigated. As an example, entering sRGB values for cyan (0/255/255) resulted in a proposal for Pantone 311 C as Best Match, giving a color difference of 17 ΔE00 between the reference values for Cyan and the reference values for the proposed Pantone 311 C. In addition, the feature to extract color code values from an uploaded photo was examined. An iPhone screenshot image of Pantone 1505 C (orange) was uploaded to Pantone Connect, which interpreted the color as being Pantone 1585 C giving a color difference of 6.3 ΔE00. The overall conclusion is that it is very uncertain and unpredictable to choose colors directly from a screen. The color differences between the color as it appears on the screen and the color as it appears on the final print can be very large and thus be the cause of the customer’s dissatisfaction, even if the customer is partly responsible. As a consequence of the lack of management and control in this area, brand color management is introduced as a new technical concept. It is an extension of traditional color management, so it also includes color selection, color specification, color description and an extended form of color control.